Erratum to: Atomic mobility in titanium grade 5 (Ti6Al4V), J. Min. Metall. Sect. B-Metall. 55 (1) B (2019) 65-77. DOI: 10.2298/JMMB180620030G (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
n/a
Keywords: n/a